Acute kidney injury on chronic kidney disease: from congestive heart failure to light chain deposition disease and cast nephropathy in multiple myeloma. Issue 4 (4th July 2019) - Shaikh, Sana; Nwankwo, Christian; Lacasse, Alexandre; Cheng, Steven
ABSTRACT: Acute on chronic renal failure is a common but notably broad diagnosis. We present a 64-year-old man with a history of diastolic heart failure and chronic kidney disease, admitted for an elevated creatinine. History and physical examination were suggestive of decompensated heart failure; however, the careful interpretation of urinalysis rendered the diagnosis of multiple myeloma. On renal biopsy, the patient was found to have light chain deposition disease with cast nephropathy. Combination lesions in multiple myeloma are rare and require diligent histopathology for detection, including light microscopy, immunofluorescence and electron microscopy. These patients portray different demographics, renal manifestations, oncologic characteristics and outcomes, and hence, further studies isolating these combined lesions are warranted. Abbreviations: CKD: chronic kidney disease; CN: cast nephropathy; CT: computerized tomography; EDD: electron-dense deposits; EM: electron microscopy; IF: immunofluorescence; FLC: free light chain; LC: light chain; LCDD: light chain deposition disease; MIDD: monoclonal immunoglobulin deposition disease; MM: multiple myeloma; LM: light microscopy; NGS: nodular glomerulosclerosis; κ: kappa; λ: lambda.